Preparation of Functionalized 2,7-Naphthyridines by Directed Lithiation with (2,2,6,6-Tetramethylpiperidyl)lithium and Their Regioselective Iron-Catalyzed Cross Couplings - Greiner, Robert; Blanc, Romain; Petermayer, Christian; Karaghiosoff, Konstantin; Knochel, Paul (Synlett, 2016)
We report the regioselective functionalization of 2,7-naphthyridines by using (2,2,6,6-tetramethylpiperidyl)lithium as a base, together with the regioselective iron-catalyzed cross-coupling reactions of the products to give tetraalkylated 2,7-naphthyridines selectively.
Keywords: lithiations; Grignard reagents; iron; catalysis; naphthyridines; alkylations